Implementation of the Policy on Rooftop Solar Power Plants (PLTS) for Residential Customers of PT Perusahaan Listrik Negara (Persero) in the Province of DKI Jakarta - Wiyanti, Ani; Zulmasyhur , Zulmasyhur (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the implementation of the Rooftop Solar Power Plant (PLTS Atap) policy for residential customers of PT PLN (Persero) in the Province of DKI Jakarta, along with its supporting and inhibiting factors. The theory used in this research is Grindle’s policy implementation theory. The research method employed a qualitative approach with a descriptive-analytical type. The results indicate that the implementation of the Rooftop Solar policy for residential customers of PT PLN (Persero) in DKI Jakarta is considered less successful. This is because the policy implementation has not fully represented the interests of the target group; the benefits generated remain limited; the expected changes have not been supported by clear operational strategies; the decision-making structure is fragmented; the capacity of implementing actors is still inadequate; resource support remains limited; power dynamics and actors’ interests have led to restrictions that slow down implementation; institutional support has not been accompanied by adequate supporting instruments; and the level of responsiveness to customers’ needs and complaints remains low. The supporting factors include public awareness of clean energy, the readiness of a competent EPC/vendor market, and PLN’s institutional commitment to service digitalization. The inhibiting factors include policy systems and financing mechanisms that have not provided attractive economic incentives, limitations in the readiness and reliability of electricity infrastructure, procedures and service mechanisms that have not ensured certainty and ease, and inconsistencies in policy direction and alignment among actors.